Measles outbreaks and public attitudes towards vaccine exemptions: some cautions and strategies for addressing vaccine hesitancy - Sandra Crouse Quinn; A. M. Jamison; V. S. Freimuth (Taylor & Francis Group, 2020)
Today, the United States and countries throughout the world are experiencing measles outbreaks that have sickened thousands of children. From the Disneyland outbreak in 2014 to today, some states have responded with changes in laws on vaccine requirements and exemptions. In this article, we examine the history of vaccine laws, and using our 2015 survey data, explore to what extent the news coverage of the Disneyland outbreak altered parents' attitudes toward required vaccination and non-medical exemptions. We explore those results in the context of today's increasing polarized and politicalized battle over vaccine laws, and consider how health care providers and policy makers can work to improve public attitudes about vaccines.